1986
DOI: 10.1128/mcb.6.8.2865
|View full text |Cite
|
Sign up to set email alerts
|

Multiple mechanisms are responsible for altered expression of ornithine decarboxylase in overproducing variant cells.

Abstract: We selected and characterized a series of mouse S49 cell variants that overproduce ornithine decarboxylase (ODC). Previously, we described variants that have an amplified ODC gene and produce about 500-fold more ODC than the wild-type cells of origin (L. McConlogue and P. Coffino, J. Biol. Chem. 258:12083-12086, 1983). We examined a series of independent variants that overproduce ODC to a lesser degree and found that a number of mechanisms other than gene amplification are responsible for the increased ODC act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
0
1

Year Published

1988
1988
1991
1991

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 36 publications
5
70
0
1
Order By: Relevance
“…Peak levels of enzymatic activity were similar in both cell types, but initial levels were higher in the transfectants expressing stable that the sequences flanking the coding region participate in regulation of ODC activity when cells are treated with serum or TPA or undergo cell-density-dependent changes in growth. We and other workers have shown that post-transcriptional and post-translational mechanisms as well as transcriptional changes determine ODC steady-state enzymatic activity [3,4,7,31,32]. (There is good evidence that indicates that enzymatic activity is exclusively determined by the number of ODC protein molecules [6,33]).…”
Section: Odc Lability and Its Effect On Regulationmentioning
confidence: 99%
See 4 more Smart Citations
“…Peak levels of enzymatic activity were similar in both cell types, but initial levels were higher in the transfectants expressing stable that the sequences flanking the coding region participate in regulation of ODC activity when cells are treated with serum or TPA or undergo cell-density-dependent changes in growth. We and other workers have shown that post-transcriptional and post-translational mechanisms as well as transcriptional changes determine ODC steady-state enzymatic activity [3,4,7,31,32]. (There is good evidence that indicates that enzymatic activity is exclusively determined by the number of ODC protein molecules [6,33]).…”
Section: Odc Lability and Its Effect On Regulationmentioning
confidence: 99%
“…The ODC assay quantitates the release of ['4C]CO2 during ODC-catalyzed conversion of ornithine to putrescine and CO2 [20]. The band marked by an asterisk is of a size consistent with that for a hamster ODC fragment as predicted by sequence comparison [46,47].…”
Section: Enzymatic Assaymentioning
confidence: 99%
See 3 more Smart Citations